Histopathological changes in intestine of chicken (Gallus domesticus) infected naturally by Ascaridia galli - Ummu Balqis; Muhammad Hambal; . Darmawi; Cut S. Utami (Syiah Kuala University, 2013)
This study was aimed at finding out the histopathological changes of chicken intestines that were naturally infected by Ascaridia galli. Ten intestines were obtained from wet market in Banda Aceh then measured in length and divided into three sections: duodenum, jejunum and ileum, of which histologicslides were made. The number of Ascaridia galli founded in the lumen and ingesta were counted. Parameter picture of histopathologycal changes were analized descriptively based on desquamation, hiperplasia, and villi fussion occure. Duodenum, jejunum and ileum infected by A. galli showed istopathological changes of villi the cover of desquamation, hyperplasia and fusion. Demage level of the small intestine chicken was largely determined by the number of infecting by A. galli. It was concluded that the more number of A galli infected to chickens, the higher level of damage would be occured in the small intestine of chicken